A literature review of the sponge-dwelling gobiid fishes of the genus Elacatinus from the western Atlantic, with description of two new Caribbean species - Randall, John E.; Lobel, Phiillip S. (Zootaxa, 2009)
Nineteen species of the neotropical gobiid genus Elacatinus are currently known from the western Atlantic, six of which are closely associated with sponges. Elacatinus colini is described as a new species of sponge-dwelling goby from Belize and Islas de la Bahía, Honduras. Formerly regarded as a color variant of E. xanthiprora (Böhlke & Robins) from Florida, it is differentiated principally by having a white instead of bright yellow stripe on the body, and 17 or 18 vs. 19 or 20 pectoral-fin rays. A second new species, E. serranilla, also formerly identified as a color form of E. xanthiprora, is described from three specimens from the Serranilla Bank in the Caribbean Sea (15°50’N, 79°50’W) and one from Jamaica (formerly a paratype of E. xanthiprora). It is distinct in having 10 dorsal soft rays (vs. 11 or 12 for E. xanthiprora), a bluish white dorsolateral stripe and median rostral band, longer dorsal-fin spines, and longer dorsal and anal soft rays. Elacatinus xanthiprora is presently known from Dry Tortugas (type locality) north to Miami in the Atlantic, and north to 28°41’N, 83°45’W on the Gulf coast of Florida, where the largest specimen (ANSP 148926, 43.1 mm SL) was collected at a depth of 26 m. Specimens off the east coast of Nicaragua in 27 m, and from nearby Isla de Providencia in 3–13 m, also previously identified as E. xanthiprora, probably represent two different undescribed species. Additional collection of specimens from the latter two localities is recommended for details of life color and DNA analysis.